PERAN MODEL PEMBELAJARAN CPS TERHADAP KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA KELAS V SD - Wulan Sutriyani; Bela Ariani; Adelia Deva Fitriana (LPPM Universitas Bina Bangsa, 2023)
This study aims to describe the ability to solve math story problems in fifth grade students at SDN 5 Ngabul Jepara. This study uses a quantitative approach by using the library research method. The data collection procedure is carried out by reading, studying and recording various literature or reading materials that are in accordance with the subject matter, then filtered and poured into a theoretical framework. Data analysis using the percentage technique. The findings of the research show that the data obtained from the first cycle with an average value of 66.93, this value does not meet the KKM limit of 70 which has been set by SDN 5 Ngabul. This is because students are still not familiar with the sequential process of learning activities using the Creative Problem Solving model. In the third cycle, the average value increased to 78.23 and the obtained DSK has also reached 87.10%, the achievement of Classical Absorption has reached the predetermined criteria, namely >85.